Application of Different Analytical Techniques and Microbiological Assays for the Analysis of Macrolide Antibiotics from Pharmaceutical Dosage Forms and Biological Matrices. (22nd August 2012) - Bekele, Lantider Kassaye; Gebeyehu, Getachew Genete
Abstract : Macrolides are a group of drugs whose activity stems from the presence of a macrolide ring, a large macrocyclic lactone ring to which one or more deoxy sugars may be attached. They are produced by Streptomyces species and used primarily against gram-positive bacteria. The determination of antibiotics, including macrolides, is mainly carried out by microbiological assays. However, microbiological assays tended to lack specificity. And hence to overcome this problem, lots of chemical and instrumental methods have been developed to determine macrolides separately as well as simultaneously. Different chromatographic, spectrophotometric, and electrochemical methods used for the determination of macrolides have been reviewed in this paper.